Reforma de la Ley de Régimen Tributario Interno referente al pago anticipado del impuesto a la renta ya que vulnera derechos constitucionales y legales del contribuyente - Bravo Paladines, José Vladimir (2015)
Under this summary of the research work carried theme "REFORM ACT OF INTERNAL TAX REGIME RELATING TO ADVANCE PAYMENT OF INCOME TAX AS VULNERABLE RIGHTS CONTITUCIONALES AND LEGAL TAXPAYER." To choose the topic sentence proceeded to review the Internal Taxation Law, specifically Article 41, and whereas the advance payment of income tax affects the liquidity of companies, is threatening several factors such as job security and economic reinvestment to make advance payments without knowing the level of utility that these have in the new financial year; thus affecting micro and macro local and national businesses and determining the constitutionality of Article 41 of the Law on Internal Taxation of the advance payment of income tax, the purpose is to inform our legal reality, about this topic because, as law students we are obliged to know and make known the true fiscal reality in which we are immersed all Ecuadorians mainly persons performing the advance payment of income tax. For research Plantie some goals as making a legal, critical and doctrinal study of the Law on Internal Taxation, as it relates to the payment of the advance income tax of natural or legal persons; likewise use several methods, techniques and instruments in the research process allowed facilitate theoretical understanding as obtaining information, tabulation and analysis of results as hiring objectives, hypothesis testing and preparation of the proposal